Possibilities of Using Pedagogical Technologies in Teaching Students to Critical Thinking - Xurramova Sanobar Mahmatmurodovna (Genius Journals, 2023)
The article describes in detail the situation and possibilities of using pedagogical technologies in teaching students to think critically.
Keywords: Opportunity, future teacher; educational technology; innovation; pedagogical technology